Beyond the glitter: gold nanoparticles as powerful weapons against multi-drug resistant pathogens - Khalifa, Hazim O.; Alkhoori, Hind (Frontiers in Molecular Biosciences, 2025)
Gold nanoparticles (AuNPs) have emerged as promising antimicrobial agents in the fight against multidrug-resistant (MDR) pathogens. Their distinctive physicochemical properties allow them to target a broad spectrum of MDR microorganisms, including highly virulent strains such as methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa, Escherichia coli, Acinetobacter baumannii, and Candida albicans. AuNPs exert potent antimicrobial effects through various mechanisms, including bacterial growth inhibition, biofilm disruption, reactive oxygen species (ROS) generation, and enhancement of conventional antibiotic efficacy. Compared to traditional antimicrobials, these nanoparticles offer key advantages such as low toxicity, high biocompatibility, and a reduced likelihood of promoting bacterial resistance. This review provides a comprehensive analysis of the antimicrobial mechanisms, synergistic interactions with antibiotics, and therapeutic potential of AuNPs. Additionally, it examines recent advancements in their clinical applications, formulation strategies, and safety profiles. Despite encouraging results, challenges persist in optimizing AuNP synthesis, evaluating their long-term effects, and ensuring their large-scale clinical translation. Future research should focus on improving nanoparticle formulations, assessing their in vivo efficacy, and conducting extensive clinical trials to confirm their therapeutic viability. Overall, AuNPs represent a promising and multifaceted approach to tackling antimicrobial resistance, offering new avenues for the development of effective treatments against MDR pathogens.